Surgical treatment of chronic pancreatitis with an inflammatory pancreatic head mass: a retrospective study - Rousek, Michael; Záruba, Pavel; Pudil, Jiří; Kšírová, Eliška; Pohnán, Radek (BMC gastroenterology, 2024)
BACKGROUND: Conservative treatment of chronic pancreatitis has only a limited effect in most patients. Surgery offers very good long-term results, even in the early stages of the disease. Unfortunately, only a minority of patients undergo surgical treatment. The aim of this work was to summarise the current treatment options for patients with an inflammatory mass of the pancreatic head. Data from patients in our study demonstrates that the surgery is a safe method, and here we compare the perioperative and early postoperative outcomes of patients who underwent a pancreatoduodenectomy and duodenum-preserving pancreatic head resection for chronic pancreatitis. METHODS: All patients who underwent a pancreaticoduodenectomy or a duodenum-preserving pancreatic head resection in our department between 2014 and 2022 were included in this study. Perioperative and early postoperative results were statistically analysed and compared. RESULTS: Thirty-eight pancreaticoduodenectomies and 23 duodenum-preserving pancreatic head resections were performed. The overall mortality was 3%, whereas the in-hospital mortality after pancreaticoduodenectomy was 5%. The mortality after duodenum-preserving pancreatic head resection was 0%. No statistically significant differences in the hospital stay, blood loss, and serious morbidity were found in either surgery. Operative time was significantly shorter in the duodenum-preserving pancreatic head resection group. CONCLUSIONS: Both pancreatoduodenectomy and duodenum-preserving pancreatic head resection are safe treatment options. Duodenum-preserving pancreatic head resection showed a statistically significant superiority in the operative time compared to pancreaticoduodenectomy. Although other monitored parameters did not show a statistically significant difference, the high risk of complications after pancreaticoduodenectomy with a mortality of 5%; maintenance of the duodenum and upper loop of jejunum, and lower risk of metabolic dysfunctions after duodenum-preserving pancreatic head resection may favour duodenum-preserving pancreatic head resection in recommended diagnoses. Attending physicians should be more encouraged to use a multidisciplinary approach to assess the suitability of surgical treatment in patients with chronic pancreatitis.
Keywords: dospělí; Pancreatitis, Chronic; Female; Operative Time; léčba šetřící orgány; Adult; výsledek terapie; ženské pohlaví; mortalita v nemocnicích; lidé; Pancreaticoduodenectomy; pooperační komplikace; pankreas; Treatment Outcome; délka pobytu; pankreatoduodenektomie; Length of Stay; retrospektivní studie; pankreatektomie; Male; Postoperative Complications; Aged; duodenum; chronická pankreatitida; Organ Sparing Treatments; délka operace; Hospital Mortality; lidé středního věku; senioři; mužské pohlaví; Pancreas; Pancreatectomy; Duodenum; Retrospective Studies; Middle Aged; Humans